Radiological appearances of hydatid disease in Wales. Issue 725 (March 1986) - Clements, R.; Gravelle, I. H.
Abstract : Thirty six patients with hydatid disease have been investigated in the Radiology Departments of Cardiff hospitals between June 1973 and June 1984; thirty two of these patients are likely to have acquired the disease in Wales. There were 16 hepatic cysts, 3 renal cysts, 2 cerebral cysts, 15 pulmonary cysts, 1 pleural cyst, 1 recurrent spinal cyst, and 1 cyst of the broad ligament. The radiological features are discussed. These patients emphasize the higher incidence of hydatid disease in Wales, compared with other regions of the United Kingdom, and the need to consider this diagnosis in Welsh patients from rural areas, who have large pulmonary opacities, or hepatic, renal, or cerebral cystic abnormalities.